Acque, fiumi e progetti utopici nel paesaggio veneto - Matteo Proto (Projets de Paysage)
The article analyzes the Utopia related to the construction of water paths in the North of Italy beginning of the nineteenth century. The revival of the internal navigation aimed at implementing projects of transformation of the Po valley and of the rivers and canals linked to it à into a main water path able to connect the main cities on the Padane plain. This article focuses on an uncompleted project, which is still subject of discussion: the Padova-Venice water path. The development project of the ancient fluvial link between the two cities has been radically modified at the end of the 1950s, when the water path has been reconsidered as the first part of a canal between Venice and Milan. The project has been developed during two decades in a context of bureaucratic and technical difficulties: among others, the progressive marginalization of the political group «Christian democracy», main partisan of the project. This initiative failure raises today the issue of reutilization of the expropriated areas in the global context of environmental and infrastructural challenges, faced by the Veneto.